Therapeutic Use of Chemokines - Hogaboam, C.M.; Bone-Larson, C.; Matsukawa, A.; Steinhauser, M.L.; Blease, K.; Lukacs, N.W.; Kunkel, S.L. (Current Pharmaceutical Design, 2000)
Chemokines are involved in a number of pathological processes, and therefore represent important targets. However, it has also become apparent that chemokines have exciting therapeutic applications in inflammatory, infectious and cancer-related diseases. The following review will highlight the application of novel therapies including viral-encoded, recombinant, and genetically engineered chemokines to a number of diseases or disorders. Advances in the application of novel chemokine delivery procedures both at the research bench and the clinical bedside will also be discussed. Overall, the utilization of chemokines to prevent and treat disease has tremendous potential.
Keywords: Oncogene